2020
DOI: 10.1038/s41419-020-2687-6
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin promotes endothelial survival by regulating eNOS activity and flow-dependent anti-apoptotic gene expression

Abstract: Increased endothelial cell (EC) apoptosis is associated with the development of atherosclerotic plaques that develop predominantly at sites exposed to disturbed flow (DF). Strategies to promote EC survival may therefore represent a novel therapeutic approach in cardiovascular disease. Nitric oxide (NO) and β-catenin have both been shown to promote cell survival and they interact in ECs as we previously demonstrated. Here we investigated the physiological role of β-catenin as a mediator of NO-induced cell survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Thus, the results of the present study suggest that the anti-tumor activity of AbM may be due to decreased cellular proliferation, but also the induction of cell apoptosis (54). This is supported by other studies that demonstrate that anti-cancer agents regulate Bcl-2 family members (including Bax or Bcl-2) (55)(56)(57). This evidence strongly supports the results of the present study, which demonstrated that FA-2-b-β induced leukemia cell apoptosis in vitro, accompanied by elevated Bax expression and decreased level of Bcl-2.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the results of the present study suggest that the anti-tumor activity of AbM may be due to decreased cellular proliferation, but also the induction of cell apoptosis (54). This is supported by other studies that demonstrate that anti-cancer agents regulate Bcl-2 family members (including Bax or Bcl-2) (55)(56)(57). This evidence strongly supports the results of the present study, which demonstrated that FA-2-b-β induced leukemia cell apoptosis in vitro, accompanied by elevated Bax expression and decreased level of Bcl-2.…”
Section: Discussionsupporting
confidence: 87%
“…Despite a high degree of similarity and functional overlap, these isoforms are not functionally identical and redundant. It is known whether GSK-3β plays a central role in various signaling pathways, such as the Wnt/β-catenin, Hedgehog, Notch, and insulin signaling pathways [41][42][43][44][45] The possible pro-angiogenic mechanism for low concentrations of ellipticine is as follows: β-catenin has a positive effect on the serine/threonine-specific protein kinase-mechanistic target of rapamycin (AKT-mTOR) pathway [37], thereby inducing endothelial nitric oxide synthase (eNOS) expression and increasing nitric oxide (NO) [46]. Additionally, an activated AKT enhances the expression of hypoxia-inducible factor-1α (HIF-1α), which has a great influence on the increase in vascular endothelial growth factor (VEGF) [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, higher or no difference in Gal-1 expression was observed in term placentas from pregnancies complicated by respectively preeclampsia or FGR [32,33]. Considering the different histopathology between early-onset and late-onset FGR (or preeclampsia), the downregulated LGALS1 expression in early-onset FGR speculatively contributes directly to placental insufficiency, while the upregulated expression observed in late-onset FGR might be secondary to relative placental-umbilical hypoxia or reduced umbilical flow [30,32,34]. Gal-1 has been suggested as an early marker of endothelial dysfunction, and dysregulated Gal-1 has been linked to poor blood pressure regulation and development of cardiovascular disease [27,28].…”
Section: Downregulated Expression Of Lgals1mentioning
confidence: 99%